Prevalência e fatores de risco associados à toxoplasmose ovina no Nordeste do Brasil - Mendonça, Carlos Eduardo D'Alencar; Barros, Sílvia Letícia Bomfim; Guimarães, Vitor Andrade Accioly; Ferraudo, Antonio Sergio [UNESP]; Munhoz, Alexandre Dias (FapUNIFESP (SciELO), 2013)
In this study, we aimed to determine the prevalence and risk factors associated to Toxoplasma gondii infection in sheep from northeastern Brazil. A total of 932 ovine serum samples from 54 properties in 19 municipalities of the state of Sergipe were collected and assayed using indirect fluorescent antibody test. The assay used antibodies against Toxoplasma gondii (IFAT-IgG) with a cutoff point of 1:64. We observed that 28.22% (263/932) of the ovine samples were serum-reactive. In a logistic regression, factors such as consumption of water directly from the source, consumption of water from a deep well, and age below 12 months were associated with protection; whereas factors such as presence of cats on the property, presence of slatted floor, and use of exchanged or borrowed breeding males were associated with infection. The studied area can be considered endemic for toxoplasmosis, so it is necessary to adopt preventive and control measures because this zoonotic infection poses risks to public health.
Prevalence and risk factors associated to ovine toxoplasmosis in northeastern Brazil
Keywords: Brazil; Risk factors; Seroepidemiology; Sheep; Toxoplasma gondii